Effect of Exercise Training on Fat Loss—Energetic Perspectives and the Role of Improved Adipose Tissue Function and Body Fat Distribution - Kolnes, Kristoffer Jensen; Petersen, Maria Houborg; Lien-Iversen, Teodor; Højlund, Kurt; Jensen, Jørgen (Frontiers in Physiology, 2021)
In obesity, abdominal fat, especially accumulation of visceral adipose tissue, increases the risk of metabolic diseases such as type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD) and non-alcoholic fatty liver disease. Excessive amount of abdominal fat is associated with adipose tissue dysfunction leading to systemic low-grade inflammation, fat overflow and ectopic lipid deposition and reduced insulin sensitivity. Physical activity is recommended as the primary prevention and treatment of obesity, T2DM and related disorders. Achieving a stable reduction in body weight with exercise training alone has not showed promising effect on a population level. Due to the high-energy content in fat, a large volume of exercise training is required to reduce weight. However, even when there is no weight loss, exercise training is an effective way to improve body composition (increase muscle mass and decrease fat), and increase insulin sensitivity and cardiorespiratory fitness. High-intensity interval training (HIIT) and sprint interval training (SIT) are time efficient exercise regimens compared to traditional continuous endurance training with low-moderate intensity. In less time, HIIT and SIT produce comparable results in reducing total fat mass as well as improving cardiorespiratory fitness and insulin sensitivity. During exercise at high intensity the main source of energy is carbohydrates, whereas exercise at low intensity utilizes predominantly fat. Thus, it appears that HIIT and SIT retain the ability to reduce fat mass despite lower fat oxidation during the exercise bouts. In this review, we look into the effect of different types of exercise training on energy expenditure and substrate oxidation during physical activity, and discuss the potential effects of exercise training on adipose tissue function and body fat distribution.